2008
DOI: 10.1080/10410230701697100
|View full text |Cite
|
Sign up to set email alerts
|

Online Participation: A Content Analysis of Differences in Utilization of Two Online Cancer Communities by Men and Women, Patients and Family Members

Abstract: The Internet provides a new modality for health communication by facilitating the creation of virtual communities. These communities have the potential to influence health behavior beyond traditional FTF support groups. This study utilized content analysis of 1,424 e-mail messages posted to 2 online cancer communities to examine uses of these groups. Findings revealed (a) similarities in the content of communication in the 2 virtual communities, (b) gender differences in participation, and (c) differences in u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
100
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(108 citation statements)
references
References 40 publications
3
100
0
Order By: Relevance
“…Although several content analyses have documented the explicit types of social support messages shared in computer-mediated contexts (Braithwaite et al, 1999;Ginossar, 2008;Keating, 2013), the unique implications associated with the reduced social cues available in these settings warrant additional attention (Caplan & Turner, 2007;Walther & Parks, 2002). In text-based environments where many of the nonverbal cues present in face-to-face interaction are reduced or eliminated, features of interaction may play a particularly important role in influencing support perceptions.…”
Section: Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Although several content analyses have documented the explicit types of social support messages shared in computer-mediated contexts (Braithwaite et al, 1999;Ginossar, 2008;Keating, 2013), the unique implications associated with the reduced social cues available in these settings warrant additional attention (Caplan & Turner, 2007;Walther & Parks, 2002). In text-based environments where many of the nonverbal cues present in face-to-face interaction are reduced or eliminated, features of interaction may play a particularly important role in influencing support perceptions.…”
Section: Hypothesesmentioning
confidence: 99%
“…A number of content analyses have been conducted to examine the types of support messages shared in computer-mediated contexts (e.g., Dunham et al, 1998;Eichhorn, 2008;Keating, 2013). Informational support and emotional support are typically the most common types of support messages found in these studies (Braithwaite et al, 1999;Coulson, Buchanan, & Aubeeluck, 2007;Ginossar, 2008;Keating, 2013).…”
Section: Social Support and Computer-mediated Communicationmentioning
confidence: 99%
“…Specifically, impact of gender on participation in online communities has been studied in, e.g., communities targeting cancer [12] and travel [40]. Women have been more actively involved in cancer communities then men [12], despite the common observation that computer-mediated communication, in general, is a male-dominant technology and privileges men [30]. In the on-line travel community [40], it has been found that men, holding age and educational level constant, have been community members for longer period of time.…”
Section: Related Workmentioning
confidence: 99%
“…They support and encourage discussion amongst members and can provide places to seek help and emotional support, which can be used to promote behaviour change [81,82].…”
Section: Virtual Communitiesmentioning
confidence: 99%